2007
DOI: 10.1080/17453670610013394
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation has no effect on the incorporation of impacted morselized bone: A bone chamber study in goats

Abstract: Background Gamma irradiation has been widely used for sterilization of bone allografts. However, gamma irradiation alters proteins. This is favorable when it reduces immunogenicity, but is undesirable when osteoinductive proteins are damaged. Although the effect of gamma irradiation on BMPs has been studied, the effect of irradiation on the process of incorporation of morselized bone chips remains unclear. We studied the effects of sterilization by gamma irradiation on the incorporation of impacted morselized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…The effect of lipid extraction from allografts, which enhances bone ingrowth, has been described before by Thorén et al (1995). The similar amounts of ingrowth in rinsed allografts and irradiated, rinsed allografts are in line with the findings of Hannink et al (2007).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The effect of lipid extraction from allografts, which enhances bone ingrowth, has been described before by Thorén et al (1995). The similar amounts of ingrowth in rinsed allografts and irradiated, rinsed allografts are in line with the findings of Hannink et al (2007).…”
Section: Discussionsupporting
confidence: 78%
“…The threaded end of the implant is screwed into the bone, allowing direct contact of the ingrowth openings with the endosteal transition from marrow into bone. To accomplish this in goats, a 1-mm-thick plate was inserted into the cap to lower the ingrowth openings through the cortex (van der Donk et al 2001, Hannink et al 2007). …”
Section: Implantsmentioning
confidence: 99%
“…This process of bone removal and new bone deposited has been called creeping-substitution. The amount of unresorbed graft remnant was higher in the unprocessed bone grafts than in the washed ones whether or not subsequently irradiated (58). This observation is consistent with an accelerate bone remodelling after irradiation.…”
Section: Osteoconductivity Of Defatted Bonesupporting
confidence: 78%
“…For example, allograft bone sterilized at 15 kGy did not compromise allograft incorporation at 4 or 6 months after implantation into rabbit femora or rat tibiae (Jinno et al 2000); yet, bone grafts irradiated at 25 kGy and implanted in the same models showed dramatically reduced rates of incorporation when compared to fresh frozen specimens, with the non union rate of irradiated graft-host bone increasing with the increasing dose of radiation (Hernigou et al 1993;Godette et al 1996;Voggenreiter et al 1996;Jinno et al 2000). However, interestingly, rinsed morcellised irradiated bone implanted into a goat model has the same incorporation as rinsed non-irradiated bone (Hannink et al 2007a).…”
Section: Irradiationmentioning
confidence: 79%
“…As discussed earlier, irradiation causes oxidation of the lipids that are thought to be toxic to osteoblasts (Moreau et al 2000) and washing has been shown to remove fat from morcellised graft, an effect that is greater for smaller particles sizes (Dunlop et al 2003). As rinsed irradiated graft has the same rate of incorporation as non irradiated morcellised graft in goats (Hannink et al 2007a) it is therefore possible that rinsing may decrease the concentration of lipids available for the formation of the toxic oxidised lipids, and thus it is possible that this step is just as important in the preparation of irradiated graft as the dose of radiation itself.…”
Section: Irradiationmentioning
confidence: 89%